2020
DOI: 10.3389/fimmu.2020.569104
|View full text |Cite
|
Sign up to set email alerts
|

Bifidobacterium animalis ssp. Lactis 420 Mitigates Autoimmune Hepatitis Through Regulating Intestinal Barrier and Liver Immune Cells

Abstract: Autoimmune hepatitis (AIH) is an immune-mediated inflammatory liver disease of uncertain cause. Accumulating evidence shows that gut microbiota and intestinal barrier play significant roles in AIH thus the gut–liver axis has important clinical significance as a potential therapeutic target. In the present study, we found that Bifidobacterium animalis ssp. lactis 420 (B420) significantly alleviated S100-induced experimental autoimmune hepatitis (EAH) and modulated the gut microbiota compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(52 citation statements)
references
References 84 publications
1
51
0
Order By: Relevance
“…Mounting evidence showed that the mechanisms of AIH were related to gut dysbiosis (Cai et al, 2017 ; Furukawa et al, 2020 ). Moreover, microbiome restoration therapies, such as probiotics, prebiotics, and fecal microbiota transplantation (FMT), can effectively improve AIH (Allegretti et al, 2019 ; Zhang et al, 2020 ). The study of gut microbiota will provide new insights into the mechanism of AIH.…”
Section: The Gut Microbiota and Con A-induced Autoimmune Hepatitismentioning
confidence: 99%
“…Mounting evidence showed that the mechanisms of AIH were related to gut dysbiosis (Cai et al, 2017 ; Furukawa et al, 2020 ). Moreover, microbiome restoration therapies, such as probiotics, prebiotics, and fecal microbiota transplantation (FMT), can effectively improve AIH (Allegretti et al, 2019 ; Zhang et al, 2020 ). The study of gut microbiota will provide new insights into the mechanism of AIH.…”
Section: The Gut Microbiota and Con A-induced Autoimmune Hepatitismentioning
confidence: 99%
“…Furthermore, patients with lower Bifidobacterium failed to achieve remission (Lv et al, 2020). Zhang et al (2020) reported that Bifidobacterium lactis 420 have beneficial functions in alleviating experimental autoimmune hepatitis. It suggested probiotics supplements may help to treat AIH in the future.…”
Section: The Microbiome In Autoimmune Hepatitismentioning
confidence: 99%
“…FGF19/FGF15 inhibits CYP7A1 expression in the liver and then decreases bile acid synthesis ( Wahlström et al, 2016 ). Moreover, all-trans retinoic acid involved in retinol metabolism can significantly activate hepatic FXR, contributing to the inhibition of CYP7A1, thereby decreasing the synthesis of bile acid ( Zhang et al, 2020 ). In this study, we found an increased deoxycholic acid (DCA) level in the feces and decreased all-trans retinoic acid levels in the liver in the CCl 4 -treated group, which was improved by SCU treatment.…”
Section: Discussionmentioning
confidence: 99%